Spies, lies, and citizenship : the hunt for nazi criminals - Barbier, Mary Kathryn (University of Nebraska Press, 2017)
"Based on information from a top-secret 2006 Justice Department report, this is the first book to explore the lives of Nazi fugitives sheltered and protected in the United States and elsewhere."--Provided by publisher.